Factors that shape Muslim consumers' purchase decisions on Pattaya Corner Products, Salatiga City - Saifudin; Kesuma , Murtadho (Nur Science Institute, 2021)
This study aims to determine the reasons behind the fluctuating sales of Pattaya Corner products using price, product quality, and promotion variables to influence purchasing decisions. Primary data was used in this study and distributed through an online questionnaire. The population in this study is people who live in Salatiga, while for the sample itself, namely consumers from Pattaya Corner, Salatiga city, as many as 106 samples. Random sampling does sampling. A quantitative approach is used in this study with validity test, reliability test, T-test and F test. The study results using SPSS version 23 show that the variables of price, product quality, and promotion both have a positive and significant effect on purchasing decisions. The price variable has an impact of 52%. For the product quality variable, it has an effect of 46%. The promotion variable has an impact of 54% and is the most dominant in making purchasing decisions.